CO2-SR technology using NiBa unsupported catalyst. Isotopic study of cyclic process of CO2 storage and in situ regeneration with CH4 - Molina-Ramírez, Sergio; Peltzer, D.; Cortés-Reyes, Marina; Herrera-Delgado, María Concepción; Larrubia-Vargas, María Ángeles; Cornaglia, L.; Alemany-Arrebola, Luis José (Elsevier, 2023)
The unsupported NiBa catalyst has been used in the CO2-SR (CO2 Storage and in situ Regeneration with CH4) cyclic technology, which allows the use of CO2 from combustion and CH4 from biogas in order to produce enriched syngas streams. The isotopic study in transient regime, using 13CO2 and CD4 instead of 12CO2 and CH4, respectively, has been performed to discriminate the different carbon and hydrogen sources and the participation of the catalyst in the pathways involved in the whole cyclic process of the integrated capture of CO2 and the regeneration with CH4. The dual functionality of the catalyst showed a high chemical retention capacity of CO2 (around 0.15 mmol CO2⋅gcat-1 ) in basic Ni-Ba intermetallic centers together with the regeneration capacity through the injection of methane yielding to H2-containing stream production. During the storage stage, the CO2 adsorption and dissociative decomposition are the main reactions together with Boudouard reaction, whereas in the regeneration step, syngas was formed via chemical CO2 reduction by CH4, besides dry methane reforming.
Keywords: Gas -- Fabricación; CO2 storage and regeneration; NiBa unsupported catalyst; Isotopic study; Reaction pathways; Syngas production